Constitutive Extracellular Polysaccharide (EPS) Production by Specific Isolates of Crocosphaera watsonii - Sohm, Jill A.; Edwards, Bethanie R.; Wilson, Brian G.; Webb, Eric A. (Frontiers in Microbiology, 2011)
Unicellular dinitrogen (N2) fixing cyanobacteria have only recently been identified in the ocean and recognized as important contributors to global N2 fixation. The only cultivated representatives of the open ocean unicellular diazotrophs are multiple isolates of Crocosphaera watsonii. Although constituents of the genus are nearly genetically identical, isolates have been described in two size classes, large ~5µm and small ~3µm cell diameters. We show here that the large size class constitutively produces substantial amounts of extracellular polysaccharides (EPS) during exponential growth, up to 10 times more than is seen in the small size class, and does so under both N2¬ fixing and non-N2 fixing conditions. The EPS production exceeds the amount produced by larger phytoplankton such as diatoms and coccolithophores by one to two orders of magnitude, is ~22% of the total particulate organic C (POC) in the culture, and is depleted in N compared to cellular material. The large difference in observed EPS production may be accounted for by consistently higher photochemical efficiency of photosystem II in the large (0.5) versus small (~0.35) strains. While it is known that Crocosphaera plays an important role in driving the biological carbon (C) pump through the input of new nitrogen (N) to the open ocean, we hypothesize that this species may also contribute directly to the C cycle through the constitutive production of EPS. Indeed, at two stations in the North Pacific Subtropical Gyre, ~70% of large Crocosphaera cells observed were embedded in EPS. The evolutionary advantage of releasing such large amounts of fixed C is still unknown, but in regions where Crocosphaera can be abundant (i.e. the warm oligotrophic ocean) this material will likely have important biogeochemical consequences.